2019
DOI: 10.1038/s41598-019-49978-1
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of tumor mass by gadolinium-loaded nanoparticles irradiated with monochromatic X-rays: Implications for the Auger therapy

Abstract: Synchrotron generated monochromatic X-rays can be precisely tuned to the K-shell energy of high Z materials resulting in the release of the Auger electrons. In this work, we have employed this mechanism to destruct tumor spheroids. We first loaded gadolinium onto the surface of mesoporous silica nanoparticles (MSNs) producing gadolinium-loaded MSN (Gd-MSN). When Gd-MSN was added to the tumor spheroids, we observed efficient uptake and uniform distribution of Gd-MSN. Gd-MSN also can be taken up into cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 29 publications
0
45
0
2
Order By: Relevance
“…A new study has shown near complete destruction of tumor spheroids of human ovarian cancer (OVCAR8) when incubated with gadolinium loaded mesoporous silica nanoparticles (Gd-MSN) prior to exposure to monochromatic 50.25 KeV X-rays. [70] It is worth noting that the Gd-MSNs accumulated in the lysosomes located close to the cell nucleus. This highlights the importance not only of the energy compatibility made possible by using tunable monochromatic beam radiation, but also by the proximity of the radiosensitizers to the nucleus in order to destroy the DNA of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…A new study has shown near complete destruction of tumor spheroids of human ovarian cancer (OVCAR8) when incubated with gadolinium loaded mesoporous silica nanoparticles (Gd-MSN) prior to exposure to monochromatic 50.25 KeV X-rays. [70] It is worth noting that the Gd-MSNs accumulated in the lysosomes located close to the cell nucleus. This highlights the importance not only of the energy compatibility made possible by using tunable monochromatic beam radiation, but also by the proximity of the radiosensitizers to the nucleus in order to destroy the DNA of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, SPring-8 synchrotron radiation facility located in Harima, Japan, was used ( Figure 1B). The storage ring is operated with a constant storage ring current of 100 mA [9]. The monochromatic X-rays from a bending magnet were shaped by horizontal and vertical slits.…”
Section: Synchrotron Generated Monochromatic X-raymentioning
confidence: 99%
“…The monochromatic X-rays from a bending magnet were shaped by horizontal and vertical slits. The incident beam size is 1.4 mm in height and 1.4 mm in width at the sample position [9].…”
Section: Synchrotron Generated Monochromatic X-raymentioning
confidence: 99%
See 1 more Smart Citation
“…X‐ray irradiation is linked to high energy electromagnetic beam inducing ionization radiation. Thus, heavy metal NPs such as gold NPs will enhance the radiation dose through an increased absorption of X‐rays, and this will lead to a subsequent ejection of electrons, known as the Auger cascade . This irradiation is noninvasive, penetrates the full body but the main drawbacks include risks for healthy tissues, complexity of use, a high cost, and a specific implementation.…”
Section: Criteria and Key Issues To Design Smart Stimuli Responsive Smentioning
confidence: 99%